(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
This study aimed to investigate the level of analytical thinking skills among eighth-grade biology and earth science teachers in public schools in Latakia. The researcher employed a descriptive method and developed a scale consisting of 30 items covering various analytical thinking skills, including prediction, comparison, classification, and drawing conclusions. The study sample comprised 40 teachers, and data were analyzed statistically using means, standard deviations, and ANOVA. The results indicated that the overall level of analytical thinking skills among the participants was high. No statistically significant differences were found in these skills based on teachers’ academic qualifications or years of experience. The study concluded by emphasizing the importance of integrating analytical thinking skills into teacher preparation programs and recommended organizing specialized training programs aimed at developing and enhancing these skills to improve the quality and effectiveness of the educational process.